Efek Infrastruktur Jalan, Listrik, PMDN (Penanaman Modal dalam Negeri) bagi Pertumbuhan PDRB di Pulau Sumatera - Wahyudi, Heru; Zapita, Jesi (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze and determine the effect of road infrastructure, electricity, domestic investment on GRDP growth on the Island of Sumatra. The data used in this study is panel data with a cross-section combination of 10 provinces and time series data from 2013-2019. Research methodology: This study uses secondary data sourced from the Badan Pusat Statistika (BPS). This study uses the Panel Data Regression Analysis method (Panel Data Regression Method) with a Fixed Random Effect (FEM) approach. Results: The results of this study indicate that electricity infrastructure and domestic investment have a positive and significant effect on the rate of GRDP growth in 10 (ten) provinces on the Island of Sumatra in 2013-2019. Meanwhile, road infrastructure has a negative and insignificant effect on the rate of GRDP growth in 10 (ten) provinces on the island of Sumatra in 2013-2019, assuming cateris paribus. Limitations: The limitation in this study to economic growth is seen in the long term at least last 10 years. Contribution: Infrastructure improvement especially road as a accommodation and transportation to help in accelerating economy activities. targeted electricity subsidies and investment types selection based on needs of each region especially the province in Sumatera.